Postoperative Alanine Aminotransferase Levels Are Associated with Outcomes in Pediatric Patients Undergoing Total Cavopulmonary Connection - Siyao Chen; Han Wang; Dandong Luo; Chongjian Zhang (MDPI AG, 2022)
Background: This single-center, retrospective study aims to determine the association between alanine aminotransferase (ALT) and outcomes in pediatric patients undergoing total cavopulmonary connection (TCPC). Methods: In total, 256 pediatric patients undergoing TCPC were included and divided into a normal-ALT group and a high-ALT group. Clinical data were collected for comparisons between groups, and risk factors of high postoperative ALT were identified by univariate and multivariate analysis. A ROC analysis of the predictive value of postoperative ALT was conducted. Results: Compared to the normal-ALT group, the members of the high-ALT group were 1.6 years older and had significantly higher preoperative creatinine and direct bilirubin levels. The high-ALT group had increased fluid overload, higher vasoactive inotropic drug scores, and inferior central venous pressure. The short-term outcomes in the high-ALT group were markedly worse: they suffered a longer duration of mechanical ventilation (MV), had a higher ICU and hospital length of stay (LOS), and higher rates of mortality, infection, and reintubation. Prolonged ICU and hospital LOS, longer MV, and reintubation were identified as independent risk factors for high postoperative ALT. Postoperative ALT was of high value in predicting reintubation, MV, ICU LOS, and mortality. Conclusions: Elevated postoperative ALT levels are associated with poor short-term outcomes in pediatric patients undergoing TCPC.